The Implementation of the community language learning (CLL) method to improve the listening and speaking skills of Arabic of class VIII students at the Al-Faruqi Kampar Islamic boarding school - Layyinatil Awaliyah; Promadi Karim; Masrun Masrun (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2025)
This experimental research uses a quantitative approach, which aims to determine whether there is a significant difference between the experimental class and the control class in improving the listening and speaking skills of class VIII students in Al-Faruqi Kampar Islamic Boarding School. The formulation of the problem in this study is